Performance Characteristics of Solid Oxide Fuel Cells with YSZ/CGO Electrolyte; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Kovalchuk A. N. Anastasia Nikolaevna; Lebedinsky A. M. Aleksey Mikhaylovich; Soloviev A. A. Andrey Aleksandrovich; Ionov I. V. Igor Vyacheslavovich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Shipilova A. V. Anna Viktorovna; Lauk A. L. Aleksandr Lukyanovich; Rombaeva M. R. Maiya (2017, 2017)
Title screen